Development of Breast Cancer Preventive Behaviors among Women in Phetchaburi Province - Songwatthanayuth, Panisara; Polin, Sarunrattana; Naimkerd, Phatchararin (Journal of The Royal Thai Army Nurses, 2021)
This research and development aimed to 1) study breast cancer preventive behaviors and factors related to promote breast cancer preventive behaviors among women in Phetchaburi Province 2) develop a model for promoting breast cancer preventive behaviors among women in Phetchaburi Province and 3) evaluate a model for promoting breast cancer preventive behaviors among women in Phetchaburi Province. The research consisted of 3 phases. Phase 1 was to explore breast cancer preventive behaviors and factors related to promote breast cancer preventive behaviors among 24 women aged 20-45 years in Phetchaburi Province by using in-depth interviews. Phase 2 was to develop a model for promoting breast cancer preventive behaviors among women in Phetchaburi Province and was tested among 8 women in Phetchaburi Province. Phase 3 was to evaluate a model among 40 women in Phetchaburi Province. Data were analyzed by using content analysis and descriptive statistics (frequency and percentage) dependent t-test and independent t-test. The results from phase 1 showed that the women had little health-promoting behaviors to prevent breast cancer. The factors involved in promoting breast cancer preventive behavior were self- regulation, families support, and getting knowledge and skills support from health care providers. In phase 2, the breast cancer preventive behavior model among women in Phetchaburi province was developed under the Bandula’s self-regulation theory and House’s social support theory. In phase 3, the results revealed that the mean scores for the breast cancer preventive behavior of the experimental group was significantly higher than the control group (p<.01). The satisfaction of the breast cancer preventive behavior among women in Phetchaburi province was at a very good level. The created model could be applied to promote healthy behaviors.